1980
DOI: 10.1080/15298668091425725
|View full text |Cite
|
Sign up to set email alerts
|

Fibrogenic potential of slags used as substitutes for sand in abrasive blasting operations

Abstract: The fibrogenic potentials of coal and copper slags used as substitutes for silica sand in abrasive blasting operations were assessed in rats. The test animals were given a single pulmonary intralobar instillation of 20 mg of test material and were sacrificed 10 months after dosing. Pulmonary fibrosis was seen in the coal slag-treated rats while no fibrosis was seen in the copper slag-treated animals. Granulomas were seen in the lungs from all treatment groups. The results of the study emphasize the need for bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
1
20
1
Order By: Relevance
“…The toxicity of the waste is determined by Toxicity Characteristic Leaching Procedure (TCLP) tests and depending on the characteristics of the waste the spent abrasive must be disposed off as solid or hazardous waste [8,11,12]. Owing to the environmental impacts of the process and waste management challenges faced for safe disposal of the wastes, United States Environmental Protection Agency (US EPA) encourages industries, businesses, and institutions to consider all pollution prevention options to aid environmentally preferable purchasing (EPP).…”
Section: Significance Of Productivity and Consumptionmentioning
confidence: 99%
“…The toxicity of the waste is determined by Toxicity Characteristic Leaching Procedure (TCLP) tests and depending on the characteristics of the waste the spent abrasive must be disposed off as solid or hazardous waste [8,11,12]. Owing to the environmental impacts of the process and waste management challenges faced for safe disposal of the wastes, United States Environmental Protection Agency (US EPA) encourages industries, businesses, and institutions to consider all pollution prevention options to aid environmentally preferable purchasing (EPP).…”
Section: Significance Of Productivity and Consumptionmentioning
confidence: 99%
“…The presence of sentinel cases of dust-related disease in coal slag workers is concerning, and suggests both the need for medical surveillance, as recommended by OSHA, and further study. Several studies in rats have demonstrated lung scarring (fibrosis) after inhalation exposure [MacKay et al 1980;Stettler et al 1995;Hubbs et al 2001]. The animal experiments provide biologic plausibility for a risk of pneumoconiosis in coal slag workers, and support the need for protection and surveillance, though the exact microscopic findings and mineral burden remain unknown.…”
Section: Medial Surveillance Datamentioning
confidence: 99%
“…Airborne emissions include particles of various sizes and particulate metals, such as arsenic, cadmium, chromium (trivalent and hexavalent), lead, manganese, nickel, titanium, and others. [5][6][7][8] A study conducted to assess the toxicity of spent abrasives showed that metal concentrations can exceed the Toxicity Characteristic Leaching Procedure criteria limits. 9 Particulate emissions are of great concern because of the potential health effects, visibility impairment, ecosystem imbalance, and esthetic damage.…”
Section: Introductionmentioning
confidence: 99%